Nuclear actin: to polymerize or not to polymerize - Hofmann, Wilma A. (The Rockefeller University Press, 2006)
The form and function of actin in the nucleus have been enigmatic for over 30 years. Recently actin has been assigned numerous functional roles in the nucleus, but its form remains a mystery. The intricate relationship between actin form and function in the cytoplasm implies that understanding the structural properties of nuclear actin is elementary to fully understanding its function. In this issue, McDonald et al. (p. 541) use fluorescence recovery after photobleaching (FRAP) to tackle the question of whether nuclear actin exists as monomers or polymers.